1992
DOI: 10.1111/j.1439-0418.1992.tb01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Predators of the banana weevil, Cosmopolites sordidus (Germar) (Col., Curculionidae) in western Kenya

Abstract: Intensive field studies conducted in the banana growing areas in western Kenya have lead to the identification of 12 predators of eggs, larvae and pupae of the banana weevil, Cosmopolites sordidus. None of the predators attacked the adult weevils and also no parasitoids were recorded. The paper briefly describes the prevalence and distribution of the predators in banana plantations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
3

Year Published

2002
2002
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 0 publications
0
13
0
3
Order By: Relevance
“…However, ant and non-ant predators for C. sordidus have been reported from Kenya (Koppenhoeffer et al, 1992), Uganda (Tinzaara et al, 1999, A. Abera, pers. commun.…”
Section: Infochemicals and Biological Control Of C Sordidusmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ant and non-ant predators for C. sordidus have been reported from Kenya (Koppenhoeffer et al, 1992), Uganda (Tinzaara et al, 1999, A. Abera, pers. commun.…”
Section: Infochemicals and Biological Control Of C Sordidusmentioning
confidence: 99%
“…), and Cuba (Roche and Abreu, 1983;Bendicho, 1987). These predators were mostly found associated with weevil environments in rotten pseudostem tissues and in larval tunnels (Koppenhoeffer et al, 1992;Tinzaara et al, 1999). Attraction of predators by the volatiles from the plant-weevil complex has not been investigated yet.…”
Section: Infochemicals and Biological Control Of C Sordidusmentioning
confidence: 99%
See 1 more Smart Citation
“…In Uganda, distribution studies showed that over 60% of the adult weevils in the banana field were associated with crop residues such as rotting pseudostem (Gold et al, 2004). The weevil has predators that have been mostly found in environments harboring weevils such as banana pseudostem traps and fermenting banana pseudostem tissue, often in larval weevil tunnels (Koppenhofer et al, 1992;Koppenhofer, 1993;Tinzaara et al, 1999;Abera, 2004). Some ant species that have the potential to control C. sordidus include Pheidole megacephala and Tetramorium guineese (Mayr) (Hymenoptera: Formicidae) (Gold et al, 2001;Abera, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some ant species that have the potential to control C. sordidus include Pheidole megacephala and Tetramorium guineese (Mayr) (Hymenoptera: Formicidae) (Gold et al, 2001;Abera, 2004). Nonant predators known to prey on weevil eggs and larvae include Dactylosternum abdominale (Fabricius) (Coleoptera: Hydrophilidae), Euborellia annulipes (Lucas) (Dermaptera: Carcinophoridae), and Thyreocephalus interocularis (Eppelscheim) (Coleoptera: Staphylinidae) (Koppenhofer et al, 1992). Of these five predator species, D. abdominale and P. megacephala are the most abundant predators in environments preferred by weevils in Uganda (Tinzaara et al, 1999;Gold et al, 2001;Abera, 2004).…”
Section: Introductionmentioning
confidence: 99%